Dynamic piezo-phototronic effect in InGaN/GaN multiple quantum wells. (July 2021) - Mo, Junsen; Hua, Qilin; Sha, Wei; Yao, Mingyue; Wang, Jiangwen; Wan, Lingyu; Zhai, Junyi; Lin, Tao; Hu, Weiguo
Abstract: Piezo-phototronic effect in flexible III-nitride optoelectronic devices is of great interest in both enhanced performance and new functionalities. This work studies the carrier dynamics in flexible InGaN/GaN multiple quantum wells under varied external stress regulation. It was observed that photoluminescence (PL) intensity and carrier lifetime varied non-monotonically with increasing external stress obtaining a maximum PL enhancement of 19%. This finding reveals the inherent mechanism of how remaining internal stress determines the optoelectronic performance throughout compensating and over-compensating for the built-in piezoelectric field in InGaN wells and will guide the further device development. Highlights: External stress was applied to InGaN/GaN multiple quantum wells by constructing them on flexible substrate. It was observed that non-monotonic variation of both photoluminescence intensity and carrier lifetime with increasing stress. That non-monotonic variation reveals how the remaining stress determines the optoelectronic performance in InGaN wells.